EROPA DALAM ASIA: ADOPSI ATAU IMITASI? ASEAN dalam Konteks Integrasi dengan Model EU - Trisnanto, Anggun (Jurnal Interaktif, 2010)
The success of European countries to form a common organization present the success of functionalism theory. Other regions in the world are pursuing to form as same as European organization. However, things to be considered are the emerge of European Union are formed through three fundamental elements. The intensity of interaction among member countries of European Union; role mode of dominant states in European Union and the common external threat when the organization formed are identified as determinant factors that forms European Union (EU). Furthermore, the strength of European integration also completed from complexity of problem whereas common action is needed to face it. In the context of duplication, ASEAN is hoped to growth to be regional organization that replicates of UE. However, it is not the simple. This paper will generally analyze the rise of UE and its strength and at the same time shortly compare to ASEAN and its different culture to European. Finally, at the end of this paper, it result with the probability of duplicating UE style to ASEAN.Key words: Regionalism, European Union, ASEAN